Vpliv industrije na regionalni razvoj Tuzelske kotlina - Nurković, Rahman (Geografski vestnik, 2006)
Several factors have greately influenced the industrial development of the Tuzla basin: a good geographical position, salt and coal mines and the Power Plant Tuzla. In the past, industry employed most workers and had therefore an important role in regional development. Today Tuzla is an old industrial center causing stagnation in regional development.
Keywords: Bosna in Hercegovina; Bosnia and Herzegovina; Tuzlanska kotlina; ekonomska geografija; industrijska geografija; regionalni razvoj; industrijski razvoj; industrija; rudarstvo; regradacija okolja; revitalizacija; sustainable development; trajnostni razvoj